Local immune response as novel disease mechanism underlying abdominal pain in patients with irritable bowel syndrome. Issue 5 (3rd September 2022) - Aguilera-Lizarraga, J.; Florens, M.; Hussein, H.; Boeckxstaens, G.
ABSTRACT: Objectives: Irritable bowel syndrome (IBS) is the most frequently diagnosed functional gastrointestinal disorder, with a prevalence of up to 25% of the global population. IBS patients suffer from abnormal abdominal pain, or visceral hypersensitivity (VHS), associated with altered bowel habits in the absence of an organic detectable cause. The pathophysiology of the disease is incompletely understood, but the dysregulation of the brain-gut axis is well established in IBS. Methods: IBS onset is mainly triggered by infectious gastroenteritis, psychological factors, and dietary factors, but genetic predispositions and intestinal dysbiosis might also play a role. Additionally, immune activation, and particularly chronic mast cell activation, have been shown to underlie the development of abdominal pain in IBS. Results: By releasing increased levels of mediators, including histamine, mast cells sensitize enteric nociceptors and lead to VHS development.Â The mechanisms underlying aberrant mast cell activation in IBS are still under investigation, but we recently showed that a local break in oral tolerance to food antigens led to IgE-mediated mast cell activation and food-induced abdominal pain in preclinical models and in IBS patients. Conclusion: The concept of food-mediated VHS highlights the potential of therapies targeting upstream mechanisms of mast cell sensitization to treat IBS.